Extraction behavior of strontium from nitric acid medium with N, N'-dimethyl-N, N'-dioctyldiglcolamide. Issue 7 (10th November 2017) - Xu, Yingbo; Gao, Yang; Zhou, Yu; Fan, Chenchen; Hou, Hongguo; Zhang, Meng
ABSTRACT: Strontium-90 ( 90 Sr), one of the most significant fission products carried into high-level waste (HLW), should preferably be separated from HLW. In this investigation, the extraction of Sr 2+ was carried out using N, N' -dimethyl- N, N' -dioctyldiglcolamide (DMDODGA) in 40/60 (V/V)% 1-octanol/kerosene or ionic liquid (IL) [C6 mim][Tf2 N]. The composition of the extracted complex between DMDODGA and HNO3 depends on the aqueous HNO3 concentration. The distribution ratio of Sr 2+ ( D Sr ) is influenced by the initial concentration of HNO3 and strontium in the aqueous phase, the concentration of DMDODGA, and temperature. The stoichiometry of Sr 2+ and DMDODGA in the extracted complex is 1:3. D Sr in the IL is two orders of magnitude higher than that in 40/60 (V/V)% 1-octanol/kerosene at lower acidity.